Aneurysmal degeneration after drug-eluting stent implantation in lower limb arteries: A systematic review and case reports - Angela Luongo; Nicola Cantile; Davide Turchino; Abdul Karim Markabaoui; Raffaele Serra; Umberto Marcello Bracale (Annals of Vascular Surgery - Brief Reports and Innovations, 2025)
Background: Paclitaxel-eluting stents (DES) are widely used in the treatment of femoropopliteal peripheral arterial disease (PAD) due to their ability to inhibit neointimal hyperplasia and reduce restenosis rates. However, recent observational data have raised concerns about delayed complications, particularly aneurysmal degeneration of the treated arterial segments. Objectives: To systematically review the incidence, anatomical distribution, mechanisms, and clinical outcomes of aneurysmal degeneration following implantation of paclitaxel-eluting stents in lower limb arteries, define its incidence, anatomical distribution, proposed mechanisms, diagnostic criteria, and therapeutic approaches and to present a representative case requiring open surgical revision 12 months post-Eluvia implantation. Methods: A PRISMA-compliant systematic review was performed including randomized trials, observational studies, and case reports describing aneurysmal degeneration after DES implantation. Data were extracted regarding stent type, lesion location, diagnostic methods, follow-up, and clinical outcomes. A clinical case of aneurysmal degeneration of the common femoral artery (CFA) following Eluvia implantation was integrated. Results: Thirteen studies were included, comprising 1 randomized controlled trial, 6 observational cohorts, 1 case series, and 5 case reports. The incidence of aneurysmal degeneration ranged from 0 % to 15.7 %, with the superficial femoral artery (SFA) being the most affected site. Conservative management was common, although some cases required open surgical treatment. Our patient underwent aneurysmectomy and bypass for CFA degeneration 12 months after DES placement. Conclusions: Aneurysmal degeneration after femoropopliteal DES implantation may be underdiagnosed and clinically relevant. Given the variability in diagnostic criteria and long-term risk, systematic surveillance and further investigation are warranted, particularly in off-label stent applications.